Chronic urticaria in the real‐life clinical practice setting in Sweden, Norway and Denmark: baseline results from the non‐interventional multicentre AWARE study. (3rd April 2017) - Thomsen, S.F.; Pritzier, E.C.; Anderson, C.D.; Vaugelade‐Baust, N.; Dodge, R.; Dahlborn, A.‐K.; Vestergaard, C.
Abstract: Background: Chronic urticaria (CU) is characterized by the recurrence of itchy hives and/or angioedema for more than 6 weeks. AWARE (A World‐wide Antihistamine‐Refractory Chronic Urticaria Patient Evaluation) is a multinational study designed to document the real‐life treatment situation, burden of disease and clinical resource usage of H1‐antihistamine‐refractory CU patients. Objective: To examine baseline data from Scandinavian AWARE patients. Methods: AWARE is a prospective, non‐interventional, multinational, umbrella design study, which includes adults (≥18 years) with a confirmed CU diagnosis (>2 months) that is refractory to H1‐antihistamines. Baseline patient characteristics, disease activity (urticaria control test [UCT]), pharmacological treatment, comorbidities and healthcare usage were documented by the treating physician. Quality of life (QoL; dermatology life quality index [DLQI]; chronic urticaria quality of life questionnaire [CU‐Q2 oL; Danish patients only]) and work productivity and activity impairment (WPAI) scores were also assessed. Results: Overall, 158 CU patients from seven centres in Denmark ( n = 80), Norway ( n = 50) and Sweden ( n = 28) were included in this baseline analysis. Mean age and BMI were 40.3 years and 26.5 kg/m 2, respectively. The majority of patients were female (69.6%), had uncontrolled CU (75.6%; UCT score <12) and had a 'spontaneous' component to their CU (61.4% CSU; 20.3% both CSU and chronic inducible urticaria). Common comorbidities included asthma (19.6%), allergic rhinitis (16.5%) and food allergies (8.2%). Overall, 60.1% of patients reported using treatments for CU including non‐sedative H1‐antihistamines (40.5%), corticosteroids (19%), montelukast (14.6%) and omalizumab (8.2%). Pharmacological treatment rates increased to 96.2% during the baseline visit. On average, patient QoL was moderately affected (mean DLQI score 7.7) and healthcare resource usage was high. Conclusion: Adult Scandinavian H1‐antihistamine‐refractory CU patients reported high rates of healthcare usage and QoL impairment. Rates of pharmacological treatment use were low before study enrolment but increased to almost 100% during the baseline visit.